Micro- and nanoscale engineering of cell signaling. - Kam, L; Shen, K; Dustin, M (2013)
It is increasingly recognized that cell signaling, as a chemical process, must be considered at the local, micrometer scale. Micro- and nanofabrication techniques provide access to these dimensions, with the potential to capture and manipulate the spatial complexity of intracellular signaling in experimental models. This review focuses on recent advances in adapting surface engineering for use with biomolecular systems that interface with cell signaling, particularly with respect to surfaces that interact with multiple receptor systems on individual cells. The utility of this conceptual and experimental approach is demonstrated in the context of epithelial cells and T lymphocytes, two systems whose ability to perform their physiological function is dramatically impacted by the convergence and balance of multiple signaling pathways.